2003
DOI: 10.1023/a:1023397724023
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The taxonomic position of acidophilic actinomycetes selectively isolated from acidic soils and litter was examined using a polyphasic approach. The distinct 16S rDNA phyletic branch formed by representative strains was equated with related monophyletic clades that corresponded to the genera Kitasatospora and Streptomyces. The acidophilic isolates also exhibited a distinctive pH profile, a unique 16S rDNA signature, and contained major amounts of LL-diaminopimelic acid, galactose and rhamnose in whole-organism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
50
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(60 citation statements)
references
References 46 publications
10
50
0
Order By: Relevance
“…The predominant menaquinones of strain MUSC 93J T were identified as MK-9(H 8 ) (42%) and MK-9(H 6 ) (35%). This finding is in agreement with the report of the study conducted by Kim et al (2003), in which the predominant menaquinones of Streptomyces are MK-9(H 8 ) and MK-9(H 6 ). The cell wall peptidoglycan was determined to contain LL-diaminopimelic acid.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…The predominant menaquinones of strain MUSC 93J T were identified as MK-9(H 8 ) (42%) and MK-9(H 6 ) (35%). This finding is in agreement with the report of the study conducted by Kim et al (2003), in which the predominant menaquinones of Streptomyces are MK-9(H 8 ) and MK-9(H 6 ). The cell wall peptidoglycan was determined to contain LL-diaminopimelic acid.…”
Section: Resultssupporting
confidence: 94%
“…The whole cell sugars were found to be glucose, mannose, and ribose. The G + C content of strain MUSC 93J T was found to be 69.9 mol%; this is within the range of 67.0–78.0 mol% described for species of the genus Streptomyces (Kim et al, 2003). …”
Section: Resultssupporting
confidence: 71%
“…They grow best at a pH between 6 and 9, with maximum growth around neutrality. However, a few strains of Streptomyces have been isolated from acidic soils (pH 3.5) (10). The first study on the effect of climate on the distribution of Actinobacteria was done by Hiltner and Strömer (11), who showed that these bacteria account for 20% of the microbial flora of the soil in spring and more than 30% in the autumn because of the large amounts of crop residues available at this time of year.…”
Section: Biology Of Actinobacteriamentioning
confidence: 99%
“…3). Whilst the majority of actinomycetes have been isolated at near neutral pH (Goodfellow and Williams 1983;Basilio et al 2003) there are numerous reports of the recovery of novel, acidophilic actinomycetes particularly of the genus Streptomyces (Kim et al 2003;Cho et al 2006;Xu et al 2006). These results provide good support for the hypothesis that long-term fertilizer inputs and pH in particular have not only changed the community structure but also the taxonomic diversity of actinobacteria in these soils.…”
Section: Discussionmentioning
confidence: 74%